INDIKATOR KEAKTIFAN BELAJAR SISWA DALAM PARTISIPASI LISAN: EFEKTIVITAS PEMBELAJARAN KOOPERATIF STAD YANG DIBANTU OLEH MEDIA WORDWALL - Nachua Qinanthi; Baharudin Baharudin (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2025)
Students’ learning activeness, particularly in the form of oral participation, constitutes a key indicator of the successful implementation of interactive and meaningful learning processes. However, empirical conditions in schools indicate that such activeness remains relatively low, largely due to instructional practices that are still dominated by one-way communication patterns. In response to this issue, the present study aims to examine the effectiveness of implementing the Student Teams Achievement Division (STAD) cooperative learning model integrated with Wordwall media in enhancing students’ learning activeness in Islamic Religious Education. This research was conducted at SMP Negeri 1 Padang Ratu using a quasi-experimental design involving two classes, namely Class VIII C as the experimental group and Class VIII F as the control group. Students’ oral activeness was measured using a questionnaire instrument that had undergone validity and reliability testing. The collected data were subsequently analyzed through normality and homogeneity tests, followed by hypothesis testing using an independent samples t-test. The results revealed a significance value (Sig. 2-tailed) of 0,039, which is lower than the threshold of 0.05, indicating a statistically significant difference between the two research groups. Furthermore, the mean score of learning activeness in the experimental class was found to be higher than that of the control class. These findings suggest that the implementation of the STAD model supported by Wordwall media is capable of creating a more active and collaborative learning environment while encouraging students’ oral engagement during the learning process. Therefore, it can be concluded that the STAD model assisted by Wordwall is effective as an alternative innovative instructional strategy for improving students’ learning activeness.